Training on Fixed Asset Depreciation Calculation for Providentia High School Students - Yanti, Yanti; Thirza, Selvyna; Valencia, Agnes (International Journal of Social Science and Community Service, 2025)
This PKM initiative was conducted in collaboration with Providentia High School, located at Jalan Kedoya Raya No. 35, West Jakarta. The primary issue addressed in this program is that students frequently encounter difficulties in answering questions related to fixed assets during accounting competitions. In response, the school requested that the PKM team provide training on types of fixed assets, depreciation methods, and depreciation calculations. To address this challenge, the PKM team from Tarumanagara University organized a Problem-Based Learning (PBL) training session on Thursday, October 24, 2024, involving 26 class XI-Science students. The implementation method of this PKM is carried out in several steps. First, the PKM Team explained material about the definition and examples of fixed assets, the application of the straight line depreciation method, declining balance method and unit of production method. Second, students are invited to work on practice questions in discussion. Finally, as feedback, the PKM Team held a quiz in the form of games with attractive prizes for the quiz winners. The results of this PKM activity indicate a significant improvement in students’ comprehension and enthusiasm for fixed asset accounting. Initially, most students were unfamiliar with the concept of fixed assets and their accounting treatment. However, after the training, they demonstrated a substantial understanding of fixed assets and the application of depreciation methods.This PKM program produced two key outputs: (1) a mandatory output in the form of a scientific publication in an ISSN-accredited journal, and (2) an additional output in the form of intellectual property rights (HKI)-eligible works.